2016
DOI: 10.1007/s00345-016-1839-x
|View full text |Cite
|
Sign up to set email alerts
|

Five-year experience with the adjustable transobturator male system for the treatment of male stress urinary incontinence: a single-center evaluation

Abstract: The treatment of male SUI using the ATOMS incontinence system achieved the best results in patients with mild and moderate incontinence. For severe incontinent patients, the system represents an efficient alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 21 publications
8
21
0
Order By: Relevance
“…Importantly, based on current guidelines, there is no general recommendation for one particular adjustable male sling and surgical procedures should be based on individual patient factors as well as surgical skills. The functional outcomes in the current study are within the range of previously published results of other adjustable male slings such as ATOMS (A.M.I., Austria) 13 or REEMEX (Neomedic, Spain) 14 …”
Section: Discussionsupporting
confidence: 86%
“…Importantly, based on current guidelines, there is no general recommendation for one particular adjustable male sling and surgical procedures should be based on individual patient factors as well as surgical skills. The functional outcomes in the current study are within the range of previously published results of other adjustable male slings such as ATOMS (A.M.I., Austria) 13 or REEMEX (Neomedic, Spain) 14 …”
Section: Discussionsupporting
confidence: 86%
“…In the original clinical description of Seweryn et al [11], ATOMS system was presented as an excellent first-or second-line treatment for mild-to-moderate male SUI, even after external irradiation. Later a singlecenter experience confirmed that ATOMS represents an efficient alternative even for severe incontinence [29]. Also, patient-reported outcomes showed ATOMS is a well-appreciated option for SUI of any severity [12].…”
Section: Discussionmentioning
confidence: 69%
“…This information is important because the follow-up reported in most studies is scarce. Some reports on outcomes refer to long-term analysis but their median follow-up is only 2 to 3 years 9,19 and other multicentre studies give even less follow-up. 8,11,12 Also, information on long-term complications, device explant, and secondary treatments are necessary.…”
Section: Discussionmentioning
confidence: 99%